Determination of Experimental Zone of Controlled Incomplete Combustion - V. I. Nazarov; V. G. Malafey (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper describes method for reduction of NOx emissions by means of burning fuel with moderate residual incomplete combustion. Experimental results at two boilers are given in the paper.